A Polarization MDCSK Modulation without PDL over Multipath Rayleigh Fading Channels - Miao, M.; Wang, L.; Rong, Yue; Xu, W. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
Traditional polarization modulations suffer from polarization dependent loss (PDL) which affects the the bit error rate (BER) performance. To solve this problem, a polarization M-ary differential chaos shift keying (P-MDCSK) modulation is proposed rather than the conventional MDCSK in this paper. In the proposed scheme, the reference signals are transmitted with polarization states first, and then the information bearing signals are modulated by selecting both phase and polarization states. The union bound of BER expression of the proposed scheme is derived and verified by simulations over both additive white Gaussian noise (AWGN) and multipath Rayleigh fading channels. Results show that the BER performance of the proposed scheme is better than that of other corresponding traditional schemes with a low computational complexity.